Islamism: Expression of Political Islam and Islamic Politics In South Sulawesi - Syahrir Karim (Universitas Islam Negeri Alauddin Makassar, 2016)
Islamic politics always plays a key role in the formation of Indonesian national identity even though at certain points Islam had to compromise in the process of establishing the identity. In spite of this, Islam has noticeably brought about strong influence to a major part of Indonesian history. This in turn gives Islam a space to significantly take part in the development of Indonesian politics up to the present time. On the other hand, the role of political parties, particularly those of the Islamic parties, will always shape the discourse of Islamic party in Indonesia. This in turn will be an indicator for the ongoing involvement of Islamic politics in Indonesia, more specifically in South Sulawesi.